ASAS KEBEBASAN BERKONTRAK DAN ASAS PROPORSIONALITAS DALAM PERJANJIAN FRANCHISE INDOMARET - Laurentina Manalu (Prodi Ilmu Hukum Fakultas Hukum Universitas Warmadewa, 2024)
The first pioneer of mini-market in Indonesia, Indomaret franchise is one of the most popular passive income companies in Indonesia. The franchisor and franchisee are bound by the Indomalette Franchise Agreement pursuant to Article 1320 of the Civil Code. However, in reality, franchise agreements are concluded unilaterally by the franchisor, and each clause is spelled out in standard clauses, so only vulnerable franchisees can choose to enter into or leave the agreement. This contradicts the theory of contract performance in the Civil Code, that is, the principle of freedom of contract that states, Article 1338, Paragraph 1 of the Civil Code, Every lawfully concluded contract is considered to be law for the person who makes it. Focus on principles. About negotiating positions. There has to be a balance between the parties. The purpose of this study is to examine the application of the principle of freedom of contract and the principle of proportionality in drafting the terms of Indomaret's franchise agreement. The research method uses legal approach with normative legal approach and qualitative descriptive data analysis with literature review, which includes primary and secondary legal materials, the main source is India Mallet franchise agreement and includes tertiary legal documentation. The findings indicate that the principle of freedom of contract is well implemented in Indomaret's franchise agreement as the entire contract is determined by the franchisor, except for the determination of the contract terms. Furthermore, applying the proportionality principle, it was found that the standard terms of Indomaret's franchise agreement contained a termination clause.